INVESTIGATING MOBILE LEARNING APPLICATIONS FOR FRENCH AND GERMAN GRAMMAR LEARNING - Eiammongkhonsakun, Sunporn (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2023)
This research aims to explore features of mobile applications and basic grammar content for French and German learning. The framework of two-step learning application development was employed to analyse the quality of the four selected applications: Babbel, Busuu, Rosetta Stone and Duolingo. Babbel and Busuu are paid applications while Rosetta Stone and Duolingo are free ones. English is used as medium instruction in all applications. The grammar part, visual and auditory forms in these applications were the focus. Surprisingly, both free and paid applications offered similar quality of basic grammar content and features. The findings of this study suggest a possible guideline for improving a better French and German application to support autonomous learners.